PENGARUH EKSPOR, IMPOR TEH DAN KURS TERHADAP CADANGAN DEVISA INDONESIA - Rizky Fadillah; Saharuddin Saharuddin; Tarmizi Abbas; Umaruddin Usman (LPPM Universitas Malikussaleh - Indonesia, 2023)
This study aims to determine whether the company's condition is efficient through the efficiency analysis test. The method used in this analysis test is non-parametric quantitative with a Data Envelope Analysis (DEA) model. The data source is based on the financial statements of agricultural companies, where the input variables include Total Assets, Liabilities, and Land, while the output variable is Sales. Processed using MaxDea software. There are 12 sample companies or DMU in this study. The results of DMU analysis using VRS output orientation assumptions show that agricultural companies on an efficiency scale of 1 are 4.